Ecology and theology in the ancient world: cross-disciplinary perspectives - Hunt, Ailsa; Marlow, Hilary ca. 20./21. Jh. (Bloomsbury classical studies monographs, 2019)
This multi-disciplinary volume brings together the voices of biblical scholars, classicists, philosophers, theologians and political theorists to explore how ecology and theology intersected in ancient thinking, both pagan, Jewish and Christian. Ecological awareness is by no means purely a modern phenomenon. Of course, melting icecaps and plastic bag charges were of no concern in antiquity: frequently what made examining your relationship with the natural world urgent was the light this shed on human relationships with the divine. For, in the ancient world, to think about ecology was also to think about theology. This ancient eco-theological thinking - whilst in many ways worlds apart from our own environmental concerns - has also had a surprisingly rich impact on modern responses to our ecological crisis. As such, the voices gathered in this volume also reflect on whether and how these ancient ideas could inform modern responses to our environment and its pressing challenges. Through multi-disciplinary conversation this volume offers a new and dynamic exploration of the intersection of ecology and theology in ancient thinking, and its living legacy